Structural Process and Impacts of Mentoring Module in Ballet Certificate Program: A Case Study on CBTS Program, Royal Academy of Dance, Malaysia - Chen, Xian Yuin; Ha, Sang Woo (Harmonia: Journal of Arts Research and Education, 2022)
This case study aims to give an overview of the structural process of dance mentoring module and investigate its impact in Malaysian dance education, exemplifying CBTS program, known as Certificate in Ballet Teaching Study. For this study, the researchers have employed Eric Parloe’s mentoring model as a theoretical tool to re-interpret the process of CBTS mentoring module. Focusing on insider’s approach, also known as the emic perspective, the researchers used qualitative methods, such as interviews, auto-ethnography, and archive analysis. To discuss the necessity of the mentoring module, the researchers have examined the structure and process of CBTS 404 Mentoring Module first. After that, this study scrutinized student-teachers’ purpose and experience while they were enrolling in the CBTS program and analyzed the influence of the mentoring module based on the perspective and experience of the currently certified mentors. Lastly, the researchers have explored the impacts of the mentoring module based on previous experience of the student-teachers and mentors. Based on these analyses, the researchers have argued that the mentoring module, CBTS404, plays an actual role in teaching how to apply acquired theoretical knowledge to practical teaching environments.